Impact of Early Acute Kidney Injury on Management and Outcome in Patients With Acute Respiratory Distress Syndrome: A Secondary Analysis of a Multicenter Observational Study*. Issue 9 (September 2019) - McNicholas, Bairbre A.; Rezoagli, Emanuele; Pham, Tài; Madotto, Fabiana; Guiard, Elsa; Fanelli, Vito; Bellani, Giacomo; Griffin, Matthew D.; Ranieri, Marco; Laffey, John G.
Abstract : Objectives: To understand the impact of mild-moderate and severe acute kidney injury in patients with acute respiratory distress syndrome. Design: Secondary analysis of the "Large Observational Study to Understand the Global Impact of Severe Acute Respiratory Failure", an international prospective cohort study of patients with severe respiratory failure. Setting: Four-hundred fifty-nine ICUs from 50 countries across five continents. Subjects: Patients with a glomerular filtration rate greater than 60 mL/min/1.73 m 2 prior to admission who fulfilled criteria of acute respiratory distress syndrome on day 1 and day 2 of acute hypoxemic respiratory failure. Interventions: Patients were categorized based on worst serum creatinine or urine output into: 1) no acute kidney injury (serum creatinine < 132 µmol/L or urine output ≥ 0.5 mL/kg/hr), 2) mild-moderate acute kidney injury (serum creatinine 132–354 µmol/L or minimum urine output between 0.3 and 0.5mL/kg/hr), or 3) severe acute kidney injury (serum creatinine > 354 µmol/L or renal replacement therapy or minimum urine output < 0.3 mL/kg/hr). Measurements and Main Results: The primary outcome was hospital mortality, whereas secondary outcomes included prevalence of acute kidney injury and characterization of acute respiratory distress syndrome risk factors and illness severity patterns, in patients with acute kidney injury versus no acute kidney injury. One-thousand nine-hundred seventy-four patients met inclusion criteria: 1, 209 (61%) with no acute kidney injury, 468 (24%) with mild-moderate acute kidney injury, and 297 (15%) with severe acute kidney injury. The impact of acute kidney injury on the ventilatory management of patients with acute respiratory distress syndrome was relatively limited, with no differences in arterial CO2 tension or in tidal or minute ventilation between the groups. Hospital mortality increased from 31% in acute respiratory distress syndrome patients with no acute kidney injury to 50% in mild-moderate acute kidney injury ( p ⩽ 0.001 vs no acute kidney injury) and 58% in severe acute kidney injury ( p ⩽ 0.001 vs no acute kidney injury and mild-moderate acute kidney injury). In multivariate analyses, both mild-moderate (odds ratio, 1.61; 95% CI, 1.24–2.09; p < 0.001) and severe (odds ratio, 2.13; 95% CI, 1.55–2.94; p < 0.001) acute kidney injury were independently associated with mortality. Conclusions: The development of acute kidney injury, even when mild-moderate in severity, is associated with a substantial increase in mortality in patients with acute respiratory distress syndrome. Abstract : Supplemental Digital Content is available in the text.